Conversation and Mediated Discourse Analysis as Discourse Approaches to Teach Speaking - Suesthi Maharani (Journal of English Language Learning, 2020)
This article aims to explore conversation analysis and mediated discourse analysis as approaches to teach speaking skills. Nowadays, the conversation becomes a never-ending case to be studied. It becomes a primary interest for language researchers since the commonly daily conversation is always interesting to be analyzed. Conversation analysis and mediated discourse analysis are practical means of teaching speaking skills in the EFL classroom. This article tried to look at the theoretical basis for conversation and mediated discourse analysis and explores the possibility of applying these discourse approaches to teach speaking. Conversation analysis theory is explained in terms of adjacency pairs, turn-taking, repair, feedback, and opening and closing. In contrast, mediated discourse analysis theory is described in the term of social action. All the issues discussed above will provide teachers with explicit instruction on how to apply conversation analysis and mediated discourse analysis to teach speaking. The discussion will lead to the possibility of using these discourse perspectives to prepare for micro and macro speaking skills.